Upgrade to Iterative Image Reconstruction (IR) in Abdominal MDCT Imaging: A Clinical Study for Detailed Parameter Optimization Beyond Vendor Recommendations Using the Adaptive Statistical Iterative Reconstruction Environment (ASIR) - Mueck, F. G.; Körner, M.; Scherr, M. K.; Geyer, L. L.; Deak, Z.; Linsenmaier, U.; Reiser, M.; Wirth, S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To compare the image quality of dose-reduced 64-row abdominal CT reconstructed at different levels of adaptive statistical iterative reconstruction (ASIR) to full-dose baseline examinations reconstructed with filtered back-projection (FBP) in a clinical setting and upgrade situation. Materials and Methods: Abdominal baseline examinations (noise index NI = 29; LightSpeed VCT XT, GE) were intra-individually compared to follow-up studies on a CT with an ASIR option (NI = 43; Discovery HD750, GE), n = 42. Standard-kernel images were calculated with ASIR blendings of 0 – 100 % in slice and volume mode, respectively. Three experienced radiologists compared the image quality of these 567 sets to their corresponding full-dose baseline examination (– 2: diagnostically inferior, – 1: inferior, 0: equal, + 1: superior, + 2: diagnostically superior). Furthermore, a phantom was scanned. Statistical analysis used the Wilcoxon – the Mann-Whitney U-test and the intra-class correlation (ICC). Results: The mean CTDIvol decreased from 19.7 ± 5.5 to 12.2 ± 4.7 mGy (p < 0.001). The ICC was 0.861. The total image quality of the dose-reduced ASIR studies was comparable to the baseline at ASIR 50 % in slice (p = 0.18) and ASIR 50 – 100 % in volume mode (p > 0.10). Volume mode performed 73 % slower than slice mode (p < 0.01). Conclusion: After the system upgrade, the vendor recommendation of ASIR 50 % in slice mode allowed for a dose reduction of 38 % in abdominal CT with comparable image quality and time expenditure. However, there is still further dose reduction potential for more complex reconstruction settings.
Keywords: abdomen; iterative reconstruction; dose reduction; ASIR; computed tomography